Kinetics of Oxidation of Metochlopramide withChloramine-T in HClO4 Medium - K. M. Meenakshi; K. Vasant Kumar Pai (E-Journal of Chemistry)
The kinetics of oxidation of metochlopramide hydrochloride (MCP) with sodium N-chloro p-toluenesulfonamide (CAT) in perchloric acid solution has been studied at 313K. The reaction rate shows a first order dependence on [CAT], fractional order on [MCP] and inverse fractional order on [H+]. There is a negative effect of dielectric constant of the solvent. The addition of the reduction product of CAT has no significant effect on the rate. The rate remained unchanged with the variation in the ionic strength of the medium. The reaction fails to induce the polymerization of acrylonitrile. Thermodynamic parameters have been computed by Arrhenius plot. The stoichiometry of the reaction was found to be 1:2 and oxidation products were identified. The Michaelis-Menten type of kinetics has been proposed. CH3C6H4SO2NHCl have been assumed to be the reactive oxidizing species. Thermodynamic parameters were computed by studying reactions at different temperatures. A mechanism consistent with observed kinetics is proposed.